Effects of Particle Size and Fines Content on Thermal Conductivity of Quartz Sands. Issue 1 (January 2015) - Zhang, Nan; Yu, Xinbao; Pradhan, Asheesh; Puppala, Anand J.
The thermal properties of soil have drawn great research attention in recent years. Thermal conductivity is the most important such property, particularly for the design of shallow geothermal systems such as energy piles and borehole thermal energy storage. A newly developed thermo–time domain reflectometry probe was used to measure the thermal conductivity of quartz sands with the peak value method. Three rounded quartz sands with different particle sizes were used in experiments to investigate the effects of particle size and fines content on thermal conductivity. Results revealed that thermal conductivity increased with increasing particle size for uniform sands. The thermal conductivity was lower in fine sands than in coarse sands under dry conditions but higher in fine sands than in coarse sands at low moisture contents. The thermal conductivity of coarse sands was increased to peak value by increasing the fine sands content to the critical fines content corresponding to maximum thermal conductivity. The critical fines content increased with a decrease in the mean grain size ratio of fine sands to coarse sands; the content also was related to the grain shape.